A comparison of central nervous system involvement in patients with classical Fabry disease or the later-onset subtype with the IVS4+919G>A mutation. Issue 1 (December 2017) - Lee, Han-Jui; Hsu, Ting-Rong; Hung, Sheng-Che; Yu, Wen-Chung; Chu, Tzu-Hung; Yang, Chia-Feng; Bizjajeva, Svetlana; Tiu, Chui-Mei; Niu, Dau-Ming
Abstract Background Patients with the later-onset IVS4+919G>A (IVS4) Fabry mutation are known to have positive central nervous system involvement compared with age- and sex-matched controls. This study compares central nervous system manifestations in patients with the IVS4 mutation or classical Fabry mutations. Methods This was a retrospective analysis of magnetic resonance imaging (MRI) data from Taiwanese patients enrolled in the Fabry Outcome Survey (sponsored by Shire; data extracted March 2015). Results Twenty-five IVS4 (19 males) and 12 (four males) classical Fabry patients underwent MRI at a median (range) age of 60.7 (45.0–70.4) and 43.0 (18.0–61.4) years, respectively. All patients received agalsidase alfa enzyme replacement therapy; two (16.7%) classical Fabry patients underwent MRI before treatment start. The pulvinar sign occurred in eight (32.0%; seven males) IVS4 and six (50.0%; three males) classical Fabry patients. Infarction occurred in eight (32.0%) IVS4 and four (33.3%) classical Fabry patients. Fazekas scores of 0, 1, 2, and 3 were found for 15 (60.0%), seven (28.0%), two (8.0%), and one (4.0%) of the IVS4 patients and for six (50.0%), four (33.3%), two (16.7%), and 0 classical Fabry patients, respectively. Abnormal height bifurcation of the basilar artery was observed in 40.0% of IVS4 and 58.3% of classical Fabry patients; abnormal laterality was observed in 4.0% of IVS4 and 16.7% of classical Fabry patients. Median (range) basilar artery diameter was 2.7 (1.4–4.0) mm in IVS4 and 3.2 (2.3–4.7) mm in classical Fabry patients (P  = 0.0293); vascular stenosis was noted in 8.3% of IVS4 patients but in no classical Fabry patients. Conclusions A similar range of MRI findings was found for both IVS4 and classical Fabry patients. Notably, basilar artery diameter was larger in classical Fabry patients than IVS4 patients.